E-learning Facilities for Teaching Secondary School Physics: Awareness, Availability and Utilization - Abiodun A. Bada; Loyiso C. Jita (Research in Social Sciences and Technology, 2021)
Secondary school physics contribute significantly to the technological development of a nation because it lays the foundation for further studies in physics. Physics is an abstract science subject that relies greatly on practical, and the crucial role played by the use of instructional materials especially, e-learning facilities in this 21st century cannot be over emphasized. This study investigates the awareness, availability and utilization of e-learning facilities among secondary school physics teachers. We adopt the descriptive survey design which involved 78 physics teachers, randomly selected from all the secondary schools in Ondo, Nigeria. A researcher designed checklist was used to collect data for this study. Three research questions were answered using descriptive statistics (frequency, percentage, mean, standard deviation) and the findings from this investigation revealed that physics teachers are aware of most of the e-learning facilities for teaching secondary school physics but only few of these facilities are readily available for teaching physics. This investigation also revealed that only one of these e-learning facilities (desktop computer) was utilized by secondary school physics teachers. This study conclude that e-learning facilities were not used in teaching secondary school physics in Ondo. Based on this findings, physics teachers are encouraged to use the few e-learning facilities that are available in secondary schools. Also, government education agencies and school management team are encouraged to further stress the importance of using the available e-learning facilities for teaching secondary school physics through in-service trainings and workshops.